Recurrence Beyond the Milan Criteria of HBV-Related Single Hepatocellular Carcinoma of 2–3 cm: Comparison of Resection and Ablation - Chen, Shuanggang; Ma, Weimei; Shen, Lujun; Wu, Ying; Qi, Han; Cao, Fei; Huang, Tao; Fan, Weijun (Frontiers in Oncology, 2021)
Background Comparison of patterns of early hepatocellular carcinoma (HCC) recurrence beyond Milan Criteria (HRBM) and identification of the independent risk factors of time to recurrence beyond Milan Criteria (TRBM) after resection or ablation can develop an optimal first-line treatment and provide more opportunities and waiting time for salvage transplantation. Methods The patterns of HRBM after first-line resection or ablation in 384 patients with single-nodule HBV-associated HCC of 2-3 cm were retrospectively analyzed by one-to-one propensity score matching (PSM) between December 2008 and December 2017. The median TRBM between resection-group and ablation-group was estimated by Kaplan–Meier curves. The Cox regression analysis and the binary logistic regression were used for identification of the independent risk factors of TRBM and the occurrence of HRBM, respectively. The abilities of HRBM and recurrence to predict overall survival (OS) were compared by the time-dependent receiver operating characteristic curves and estimated area under the curve. Results Of 384 patients enrolled in our study, 260 (67.7%) received resection (resection-group) and 124 (32.3%) underwent ablation (ablation-group). The median TRBM in resection-group was significantly longer than that in ablation-group before PSM (median, not available vs. 101.4months, P<0.001) and after PSM (median, not available vs. 85.7months, P<0.001). Cox regression showed ablation, older age, CRP≥1.81mg/L and PLT≤80×109/L were the independent risk factors of TRBM. The binary logistic regression also showed that ablation, CRP≥1.81mg/L and PLT≤80×109/L were the independent risk factors of the occurrence of HRBM. The incidences of various phenotypes of HRBM were not significantly different between the two groups, but the incidence of HRBM at the first recurrence in ablation-group was significantly higher than that in the resection-group (P<0.05). Besides, compared with recurrence, HRBM was a better predictor of OS (P<0.05). Conclusions Compared with ablation, resection should be considered as a more appropriate first-line option for patients with single-nodule HBV-associated HCC of 2-3 cm and a more promising bridge for liver transplantation in those patients.